Parenting stress and pandemic burden in families with crying, sleeping, and feeding problems during COVID-19: a case-control study - Michaela Augustin; Bernhard Haller; Volker Mall; Ina Nehring; Maria Licata-Dandel; Anna Friedmann (BMC Psychology)
Abstract Background Families with child crying, sleeping, and feeding problems are a vulnerable group due to high levels of parenting stress and an increased risk for child abuse. However, little is known about their specific situation during the COVID-19 pandemic. The aim of our study was to assess parenting stress and pandemic burden / constraints in families with child crying, sleeping, and feeding problems (= clinical sample) compared to a non-clinical sample. First, we hypothesized that parenting stress during the pandemic would be higher in the clinical sample compared to the nonclinical sample. Moreover, we aimed to explore the extent to which pandemic-related burden / constraints were perceived as restrictive and whether they differed between the two groups. Last, we intended to explore which pandemic-related constraints were associated with parenting stress during the pandemic, controlled for demographic variables. Methods Using a case-control matched design, standardized questionnaire data from N = 142 parents of children aged 0–24 months, drawn from two different studies (clinical sample: n = 71, nonclinical sample: n = 71) were analyzed. Groups were compared using paired sample t-tests and variables associated with parenting stress were analyzed using a multiple linear regression model. Results Parenting stress (p <.001, d z =0.64) and overall pandemic burden (p =.034, d z =0.26) were higher in the clinical group compared to the nonclinical group, whereas groups did not differ significantly in terms of specific pandemic-related constraints. Both groups reported being burdened especially by restricted leisure activities (79.6%) and reduced family support services (74%). Parenting stress was associated with child age (β=-0.20, p =.024), the presence of siblings (β=-0.21, p =.034), overall pandemic burden (β = 0.25, p =.009), increased childcare responsibilities (β = 0.19, p =.046), and increased family conflicts (β = 0.29, p <.001). Conclusions Families with crying, sleeping, and feeding problems experienced high levels of parenting stress and were significantly burdened by the pandemic itself. Thus, as a double-risk group during the pandemic, they require targeted attention in prevention and intervention efforts, including access to professional support and opportunities for safe social connection and leisure activities. Trial registration Clinical group: German Register of Clinical Studies DRKS00019001, registration date: 2020-01-28, nonclinical group: OSF, https://osf.io/tksh5 , registration date: 2021-01-15.